My Health in My Hands: Improving Medication Abortion Knowledge and Closing Disparities with a Community-Led Media Intervention - Hayley V. McMahon; Leslie Serrano; Teja Vyavahare; Indya Hairston; Sequoia Ayala; Zainab Jah; Tiffany Hailstorks; Dázon D. Diallo; Elizabeth A. Mosley (Health Equity)
Purpose: Inaccurate beliefs about medication abortion (MA) are common. This study evaluated pilot data from a community-led media intervention designed to increase MA knowledge among Black and Latinx women in Georgia. Methods: Participants (N=855) viewed the intervention video and completed pre–post surveys. Data were analyzed using linear and logistic regression. Results: Knowledge scores significantly increased from 3.88/5.00 to 4.47/5.00. Participants who were Native American, Asian and Pacific Islander, multiracial, Black, <20 years old, and living in Georgia scored below the sample mean at baseline; however, nearly all disparities disappeared after intervention exposure. Conclusions: This intervention effectively increased MA knowledge and narrowed racial/ethnic, age-based, and geographic disparities.